Cost optimal building renovation with a net zero energy target for the Portuguese single-family building stock built before 1960 - Almeida, Manuela Guedes de (2013)
Cost Optimality and nearly Zero Energy Buildings (nZEB) are two fundamental concepts within the current European Union policy related to the energy performance of buildings and consequently related to climate change mitigation and non-renewable resources con-sumption. While Cost Optimality is mainly focused on costs, nZEB are focused on low energy consumption levels and on site renewables harvesting. If the differences between Cost Optimality and nZEB approaches result in major differences in the selection of the best package of renovation measures, the transition from the Cost Optimal concept to nZEB might result incompatible. In this context, using a virtual building representing the Portuguese residential building stock from the 20th century prior to 1960, this study investigates the most cost-effective packages of renovation measures to achieve a zero energy balance building and compares these packages with those resulting from the calculation of cost-optimal levels. Investigating the trade-offs between a renovation towards zero energy balance and a cost optimal renovation without the use of renewables is relevant to achieve a smooth transition from Cost Optimal levels to nearly Zero Energy Buildings.